2022
DOI: 10.3389/fnmol.2022.930599
|View full text |Cite
|
Sign up to set email alerts
|

Activation of the GABA-alpha receptor by berberine rescues retinal ganglion cells to attenuate experimental diabetic retinopathy

Abstract: PurposeThe aim of this study was to investigate the role and mechanism of berberine (BBR) in the protection of injured retinal ganglion cells (RGCs) in diabetic retinopathy (DR).MethodsExperimental diabetic retinopathy rat model was successfully induced by a single intraperitoneal injection of streptozotocin (STZ, 60 mg/kg) in male SD rats with sufficient food and water for 8 weeks. Animals were randomly divided into four groups: (1) non-diabetic, (2) diabetic, (3) diabetic + BBR + PBS, and (4) diabetic + BBR … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 67 publications
0
3
0
2
Order By: Relevance
“…[ 110 ] Fang found that Berberine potently defended against RGC apoptosis in the retina of rodent diabetic animals, and its defensive effect might be linked to the GABAARs/protein kinase C-α pathway activation. [ 111 ] In conclusion, traditional Chinese medicine monomer can reduce the optic nerve injury of diabetes retinopathy by regulating apoptosis.…”
Section: Resultsmentioning
confidence: 99%
“…[ 110 ] Fang found that Berberine potently defended against RGC apoptosis in the retina of rodent diabetic animals, and its defensive effect might be linked to the GABAARs/protein kinase C-α pathway activation. [ 111 ] In conclusion, traditional Chinese medicine monomer can reduce the optic nerve injury of diabetes retinopathy by regulating apoptosis.…”
Section: Resultsmentioning
confidence: 99%
“…In fact, diabetic RGCs showed a reduction in the activity and levels of these receptors. It was shown that feeding diabetic rats with berberine increased the levels of GABA receptors, decreasing RGC apoptosis [65]. In addition to RGCs, Müller cells have a prominent role in the pathogenesis of DR. Müller cells are the main glial cells of the retina, and they provide nutritional and regulatory support to the retinal neurons (▶ Fig.…”
Section: Berberine An Isoquinoline Alkaloidmentioning
confidence: 99%
“…В експерименті була показана наявність ГАМК-рецепторів на амакринових та гангліонарних нейронах сітківки [30]. При цьому при експериментальній ДР показано зниження вивільнення ГАМК та дофаміну у сітківці на тлі значного збільшення вмісту глутамату [14,31]. Посилення імунореактивності глутаматних NMDA-рецепторів спостерігалося в гангліозних, амакринових і біполярних клітинах, а також у внутрішньому і зовнішньому плексиформних шарах сітківки при експериментальному стрептозотоциновому діабеті у щурів [32].…”
Section: обговоренняunclassified